Exploration of abnormal dynamic spontaneous brain activity in patients with high myopia via dynamic regional homogeneity analysis - Ji, Yu; Cheng, Qi; Fu, Wen-wen; Zhong, Pei-pei; Huang, Shui-qin; Chen, Xiao-lin; Wu, Xiao-rong (Frontiers in Human Neuroscience, 2022)
Abstract Aim: Patients with high myopia (HM) reportedly exhibit changes in functional brain activity, but the mechanism underlying such changes is unclear. This study was conducted to observe differences in dynamic spontaneous brain activity between HM patients and healthy controls (HCs) via dynamic regional homogeneity (dReHo) analysis. Methods: Resting-state functional magnetic resonance imaging scans were performed on 82 HM patients and 59 HCs who were closely matched for age, sex, and weight. The dReHo approach was used to assess local dynamic activity in the human brain. The association between mean dReHo signal values and clinical symptoms in distinct brain areas in HM patients was determined via correlation analysis. Results: In the left fusiform gyrus (L-FG), right inferior temporal gyrus (R-ITG), right Rolandic operculum (R-ROL), right postcentral gyrus (R-PoCG), and right precentral gyrus (R-PreCG), dReHo values were significantly greater in HM patients than in HCs. Conclusion: HM patients have distinct functional changes in various brain regions, mainly including the L-FG, R-ITG, R-ROL, R-PoCG and R-PreCG. These findings constitute important evidence for the roles of brain networks in the pathophysiological mechanisms of HM and may aid in the diagnosis of HM. Key words: high myopia, brain function, brain region, resting-state functional magnetic resonance imaging, dynamic regional homogeneity